Some profiles of diabetic CKD patients with AVF on haemodialysis - Zainab Abbass Hassan (مجلة علوم ذي قار, 2019)
Background: Diabetes mellitus is one of the major chronic non communicable diseases that affect millions globally.  Diabetic nephropathy is a serious complication of diabetes mellitus, often leading to end stage kidney disease (CKD). Objectives: The aim of this study was to assess some profiles of diabetic end stage kidney disease patients with AVF on haemodialysis at baseline and adequacy of treatment after three months follow up regarding different clinical and laboratory parameters.  Methodology: The current prospective study was carried out in the haemodialysis unit in AL-Hussein Teaching Hospital (Iraq / Thi-Qar) from April to July 2016.  The   number of patients included in the study was (24) patients.  Results: The majority of patients were not educated and 50 % of them were smokers. The adherence rate of the patients with haemodialysis schedule was 50%. The prevalence of HCV infection was significantly higher among adherent than non-adherent patients. Conclusion: The management of diabetic end stage kidney disease patients with AVF on maintenance haemodialysis is considered inadequate and there was a high rate of acquiring viral hepatitis C infection after beginning sessions of hemodialysis.